al-Taʿrīb fī al-Muṣṭalaḥāt al-Iliktruniyyah wa al-Ṣiḥḥiyyah bi Mauqiʿ mawdoo3.com al-ʿArabiy - Habri Habri; Khafid Roziki; Abdul Muntaqim Al Anshory (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
The development of modern science and technology today makes Arabic have to adapt to new terms that appear. Arabic absorbs foreign words and phrases and becomes part of Arabic through several processes, including the ta'rib process. This study aims to determine the words or terms that indicate the form of ta'rib in electronics and health fields on the mawdoo3.com website and the methods used in the ta'rib process. This research is a qualitative descriptive study with a literature study approach. Data collection techniques used are reading, note-taking, and documentation techniques. The steps in analyzing the data are collecting data from the website, choosing the word or term ta'rib, describing the data and classifying it in tabular form, and drawing conclusions. The study's results revealed that on the mawdoo3.com website, 61 data were showing the words and terms of ta'rib. The method used in the ta'rib process is the translation method with 41 data, iqtibas lafdzi form with 10 data, isytiqaq method with 9 data, and naht method with 1 data.كان تطور العلوم والتكنولوجيا الحديثة اليوم يجعل اللغة العربية مضطرة للتكيف مع المصطلحات الجديدة. تمتص اللغة العربية الكلمات والمصطلحات الأجنبية وتصبح لغة عربية من خلال عدة عمليات ، بما في ذلك عملية التعريب. تهدف هذه الدراسة إلى تحليل الكلمات أو المصطلحات التي تدل على شكل التعريب في المجالات الإلكترونية والصحية على موقع mawdoo3.com العربي، والطرق المستخدمة في عملية التعريب. هذا البحث بحث وصفي نوعي مع دراسة مكتبية. تقنيات جمع البيانات المستخدمة هي تقنيات القراءة والتدوين والتوثيق. تتمثل خطوات تحليل البيانات في جمع البيانات من الموقع واختيار كلمات أومصطلحات التعريب ووصف البيانات وتصنيفها في شكل جدول واستخلاص النتائج. وكشفت نتائج الدراسة على موقع mawdoo3.com أن هناك 61 بيانات توضح كلمات ومصطلحات التعريب. الطريقة المستخدمة في عملية التعريب هي طريقة الترجمة مع 41 بيانات، وطريقة الإقتباس اللفظي في 10 بيانات، وطريقة الإشتقاق في 9 بيانات، وطريقة النحت في بيانات واحدة.